“We wove a web in childhood” Angria Revisited: A. S. Byatt’s The Game - Jane Silvey (Revue LISA)
Many women writers have been fascinated with Charlotte Brontë’s life and their admiration for her work has infected their own creative writing. The Game is a  complex and profoundly and self-consciously ‘literary’ novel in which A.S. Byatt takes the Brontë myth and uses it to reflect on the nature and power of the creative imagination. She explores how that imagination can become an overwhelming and ultimately destructive force in the lives of reading and brooding female selves. A work of extraordinary intelligence as well as of emotional intensity, its literary illusions play a vital part in the novel’s rich density of implication.